UTILIZATION OF MILLET FLOUR AS THE BASIC MATERIAL TO MAKE A MILLCOFF CAKE (MILLET COFFEE CAKE) - Titin Hera Widi Handayani, Putri Sigar Nur Azzizah (Prosiding Pendidikan Teknik Boga Busana, 2020)
Indonesia is rich in local food sources of cereals, but imports of wheat continues to rise each year. Substitution of wheat flour is one solution to cope with the high number of imported wheat. The cereals that can be used as a substitute material is millet.The purpose of this study is to determine the right recipe, knowing the nutrient content and determine consumer acceptance of millcoff cake. Millcoff cake is a product made from sponge cake flavored coffee that is substituted with millet flour and filling with avocado mouse. This type of research is the research and development with 4D development model (Define, Design, Develop and Desimination). Selection of the recipe selected based on the sensory properties of the 4 aspects of color, taste, texture and aroma. Furthermore, the 3 treatments on prescription elected in substitution of millet flour that is 30%, 40% and 50%. The results showed that the chosen cake is cake with millet flour substitution as much as 50% because it has characteristics which approach control and still be acceptable to consumers.carbohydrate 17.9897% 7.6541% protein content, fat content of 14.6541% 53.0830% moisture content and ash content of 0.9202%. Keywords: Millet Flour, Sponge Cake, Coffee Powder